Medial Branch Radiofrequency Treatment for Low-Back Pain in Cancer Patients: A Case Series - Ye Sull Kim; Taehoon Kim; Youngkwan Lee; Yu Jin Oh; Jeongmin Oh; A Ram Doo (Palliative Medicine Reports, 2022)
Cancer patients are increasing in number, with an increased lifespan and advances in cancer treatment. Palliative care physicians often encounter difficulties in caring for patients with pain. In addition to cancer-related pain, patients with cancer may suffer from various musculoskeletal diseases, resulting in significant functional limitations of physical activities of daily living. We present three cases illustrating methods to deal with nonspecific mechanical low-back pain in patients with advanced cancer. We provide our therapeutic experiences, focusing on the usefulness of radiofrequency treatment in palliative care in patients with cancer.